2009
DOI: 10.5585/exacta.v6i1.712
|View full text |Cite
|
Sign up to set email alerts
|

Hidrodinâmica de uma coluna de adsorção em leito expandido para uso em purificação de proteínas de malte de milho (Zea mays)

Abstract: Neste trabalho, estudou-se o comportamento hidrodinâmico de uma coluna de adsorção em leito expandido com o objetivo de obter as condições ótimas para recuperação de amilases do malte de milho. Usou-se a resina de troca iônica Amberlite IRA 410, o tampão fosfato pH 6 em 0,07 M, sem e com 2 % do malte de milho, e água destilada como líquidos fluidizantes, nas temperaturas 295,15 ± 1 K e 301,15 ± 1 K. A equação de Richardson-Zack se ajustou perfeitamente à descrição do comportamento da fluidização dos adsorvente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…It can be observed that the errors between the velocities are lower and they are associated with experimental measurement viscosity and specific mass and the reliability of the data in the table. The low error suggests that the Richardson-Zaki equation is the best empirical model to predict the hydrodynamic behavior of adsorbent particles in expanded bed systems, even when the fluidizer contains a larger amount of biological material in suspension [18,19,23,25,26,[28][29][30][31]. The fluidized particle end velocity decreased when the salt and biological materials were added.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It can be observed that the errors between the velocities are lower and they are associated with experimental measurement viscosity and specific mass and the reliability of the data in the table. The low error suggests that the Richardson-Zaki equation is the best empirical model to predict the hydrodynamic behavior of adsorbent particles in expanded bed systems, even when the fluidizer contains a larger amount of biological material in suspension [18,19,23,25,26,[28][29][30][31]. The fluidized particle end velocity decreased when the salt and biological materials were added.…”
Section: Resultsmentioning
confidence: 99%
“…It introduces the concept that there is a stronger resistance of resin bed in order water (H 2 O) > phosphate buffer (PhB) > biomoleule + buffer (BB). For the fluidizer containing maize malt and salts, there was a large effect of friction on degree of expansion for the particle-particle, particle-liquid and particle-biomolecule interactions, which provoked an increase in the linear velocity of the fluidizer to maintain the bed voidage at the same level as that in the salt system [17,18,[24][25][26][27][28][29][30][31]. Analyzing these figures, it can be observed that the values of Richardson-Zaki index decreased in relation to temperature and to the addition of salt and of biomolecules.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations